Effects of fermented Rosa roxburghii Tratt pomace on growth performance, lipid metabolism, antioxidant activity, and amino and fatty acid profile in goats - Rui Chen; Fu Wang; Shuanglong Xie; Yiming Ban; Chengcheng Gao; Peiyao Li; Jixiao Qin; Yiqing Xu; Qi Lu; Xu Wang; Xingzhou Tian (PLoS ONE, 2026)
Rosa roxburghii Tratt pomace, is a juice extraction rich in polyphenols with strong antioxidant activity. The objective of this study was to evaluate the effect of fermented Rosa roxburghii Tratt pomace (FRRT) on growth performance, plasma biochemistry and antioxidant status, and longissimus dorsi muscle amino- and fatty-acid profiles in meat goats. Twenty-four goats with similar body weights (30.7 ± 4.71 kg) were allotted in a completely randomized design to either basal diet (CON) or the same diet containing 7% (LF) or14% (HF) of FRRT on a total mixed ration (TMR) dry matter (DM) basis for 60 d following 14 d adaptation. FRRT did not alter dry matter intake or average daily weight gain, but reduced ( P < 0.05) the feed conversion ratio (FCR) compared to CON. Plasma creatinine and total cholesterol increased ( P < 0.05) with FRRT, while low-density lipoprotein cholesterol (LDL-C) was numerically higher in the HF group (overall P = 0.069). FRRT increased ( P < 0.05) the plasma total antioxidant capacity and catalase; malondialdehyde tended to be lower ( P = 0.067) HF group than CON. In muscle, the 14% FRRT diet increased essential, non-essential, flavor and total amino acids ( P < 0.05), with higher concentrations of several individual amino acids (e.g., threonine, serine, glycine, tyrosine, lysine, arginine). Among fatty acids, C15:0 decreased in 7% FRRT ( P < 0.05) and arachidonic acid (C20:4n-6) increased ( P < 0.05), whereas sums of SFA, MUFA and PUFA did not differ. In conclusion, 7–14% FRRT (DM basis) improved feed efficiency and antioxidant status and favorably modified selected muscle amino- and fatty-acid traits, but elevated circulating cholesterol; the lipid responses warrant further study.